Selected Topics on Advances in Capability-Oriented Information Systems Development: Editorial Introduction to Issue 10 of CSIMQ - Jelena Zdravkovic; Óscar Pastor; Peri Loucopoulos (Complex Systems Informatics and Modeling Quarterly)
Modern organizations need to be sustainable in the presence of dynamically changing business conditions, which require from Information Systems (IS) to address complex challenges for being able to support organizations acting in varying business conditions – changing customer demands, new legislations, new customers, and emerging alliances. From a technical perspective, the gap between business requirements and supporting IS is still present, mostly due to the fact that current IS development approaches operate with artifacts defined on a relatively low abstraction level. To go beyond the state of the art, IS development frameworks used by enterprises need to be structured for solving emerging problems, and enterprises need to have efficient methods for the use of these frameworks to deliver the right IS solutions just-in-time and just-enough. The notion of capability emerged in the beginning of the nineties in the context of competence-based management, military frameworks, and developing organization’s competitive advantage – linguistically, it means the ability or qualities necessary to do something.